Association between physician‐staffed ambulances and patient prognoses after out‐of‐hospital cardiac arrests with respect to shockable and non‐shockable rhythms: a retrospective observational study in a southern area of Shiga Prefecture Japan - Kato, Fumitaka (Acute Med Surg, 2019)
AIM: Out‐of‐hospital cardiac arrests (OHCA) are a significant public health problem; to improve patients’ prognoses, various interventions, such as providing physician‐staffed ambulances, have been implemented. We aimed to examine whether physician‐staffed ambulances were associated with patients’ prognoses after OHCA with respect to first‐monitored rhythms. METHODS: This retrospective observational study was undertaken between 1 September 2011 and 31 December 2015, using data based on Utstein‐style guidelines. We extracted data on age, sex, first‐monitored rhythm (shockable or non‐shockable), presence of a witness, bystander cardiopulmonary resuscitation, time from call to arrival at the scene, out‐of‐hospital adrenaline administration, out‐of‐hospital intubation, return of spontaneous circulation before arrival at the hospital, and survival and neurological outcomes 30 days after OHCA, according to cerebral performance categories. We undertook logistic regression analyses to assess the association between physician‐staffed ambulances and patients’ prognoses. RESULTS: A total of 882 OHCA patients were eligible for this study. Physician‐staffed ambulances attended to 164 OHCA patients. Multivariable analysis found that in non‐shockable rhythm patients, physician‐staffed ambulances significantly improved good neurological outcome (odds ratio, 3.65; 95% confidence interval [CI], 1.28–10.50; P = 0.02), return of spontaneous circulation before arrival at the hospital (odds ratio, 2.68; 95% CI, 1.62–4.42; P < 0.001), and 30‐day survival (odds ratio, 2.90; 95% CI, 1.30–6.45; P = 0.009). However, physician‐staffed ambulances were not associated with patient prognoses in shockable rhythm patients. CONCLUSION: Despite our study's limitations, physician‐staffed ambulances might be associated with good neurological outcomes in non‐shockable rhythm patients. Our observations could provide more appropriate prehospital treatment options for OHCA patients.